Beliefs about the factors that motivate prosocial sentiments among people in the privileged class of Pakistan during the COVID‐19 pandemic. (30th May 2022) - Ahmed, Ahsan Mehmood; Rasool, Shahid; Prentice, Catherine; Ahmad, Muhammad Hissan
Abstract: Drawing upon the theories of empathy‐altruism and planned behavior, this study investigated beliefs about the factors that motivate prosocial sentiments among people in the privileged class of Pakistan during the COVID‐19 pandemic. In‐depth interviews were conducted with 31 participants who were deemed to be members of the privileged class within the class system of Pakistan. The results revealed nine themes including social interaction, peer influence, role models, collectivism, vicarious emotions, religiosity, capability, volition, and education.